Synthesis, characterization and antimicrobial studies of imine derivatives of amoxicillin - Islam, Muhammad; Shafiq, Zahid; Hussain, Mazhar; Ahmad, Hafiz Badaruddin; Hussain, Muhammad Ajaz (European Journal of Chemistry, 2015)
Some novel imine derivatives (1-14) of a broad spectrum antibiotic amoxicillin were prepared by condensation with different carbonyl compounds. The amoxicillin imine derivatives were characterized using elemental analysis and spectroscopic techniques such as FT-IR and 1H NMR. The prepared imine derivatives were evaluated for antimicrobial activities against some pathogens using disc diffusion method. The results of present studies demonstrate enhanced antimicrobial activity of the novel imine derivatives of amoxicillin as compared to the parent drug.